2019
DOI: 10.1039/c8tc02993h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of end group functionalisation of small molecules featuring the fluorene–thiophene–benzothiadiazole motif as emitters in solution-processed red and orange organic light-emitting diodes

Abstract: A series of red fluorescent materials (compounds 1-4), which each contain the symmetric fluorene-thiophene-BT-thiophene-fluorene core, is presented along with their performance in solution-processed OLED devices.Extending the molecular conjugation through end-capping with additional fluorene units (compound 2), or through incorporation of donor functionalities (compounds 3 and 4) improves OLED performance relative to the parent compound 1. Notably, incorporating triphenylamine donor groups in compound 3 led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In this work, we explore the performance of larger oligofluorene analogues to see how the molecular size affects device performance. Previous reports of fluorene‐containing small molecules or oligomers have shown that the number of fluorene groups can influence OLED characteristics such as maximum luminance, efficiency and roll‐off, and turn‐on voltage [5b,11] . In this study, we show that the length of the arms attached influences the luminance, efficiency and lifetime of the OLED devices.…”
Section: Introductionsupporting
confidence: 55%
“…In this work, we explore the performance of larger oligofluorene analogues to see how the molecular size affects device performance. Previous reports of fluorene‐containing small molecules or oligomers have shown that the number of fluorene groups can influence OLED characteristics such as maximum luminance, efficiency and roll‐off, and turn‐on voltage [5b,11] . In this study, we show that the length of the arms attached influences the luminance, efficiency and lifetime of the OLED devices.…”
Section: Introductionsupporting
confidence: 55%
“…On the other hand, the flat topology of this moiety together with the presence of chalcogen and nitrogen atoms in its structure confers this moiety a strong tendency to establish cooperative intermolecular interactions such as chalcogen bonding and π–π stacking. Thanks to their impressive optical properties BTD derivatives have been widely used as components in the fabrication of organic light-emitting diodes (OLEDs), 12 organic solar cells (OSCs), 13 bioimaging, 14 fluorescence sensing, 15 and stimuli-responsive fluorophores, 16,17 and fluorescent lysosome-staining agents 18 among others.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, the lasing wavelength of Tr3D showed 27 nm redshifts compared with Tr3, which was in accordance with the trend of the PL and ASE spectra. This end-capping strategy [58,59] has great potential for developing high-efficiency organic laser materials for optoelectronics, and it may offer renewed hope for high-performance organic lasing.…”
Section: Resultsmentioning
confidence: 99%